2008
DOI: 10.2151/sola.2008-012
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analyses of Snowfall Distribution in the Niigata Area and its Relationship to the Wind Distribution

Abstract: Analyses of precipitation amounts and surface winds observed at weather stations were conducted to investigate the effect of the topography on the snowfall distribution in Niigata. The topographic effect on the precipitation, particularly in the Niigata plain, has not been well discussed although Akiyama (1981aAkiyama ( , 1981b discussed the relationship between the snowfall distribution in Niigata and the synoptic scale condition. Using an empirical orthogonal function analysis, the winter precipitation distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
4
13
0
Order By: Relevance
“…Previous studies have reported a large spatial variation of snow cover in coastal areas of the Japan Sea (Nakai and Iwamoto 2006;Iwamoto et al 2008). ADSD also has annual and seasonal variation in coastal area (Wakabayashi et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have reported a large spatial variation of snow cover in coastal areas of the Japan Sea (Nakai and Iwamoto 2006;Iwamoto et al 2008). ADSD also has annual and seasonal variation in coastal area (Wakabayashi et al 2007).…”
Section: Introductionmentioning
confidence: 94%
“…In the M-type climatological winter monsoon pattern, the high pressure in the west of Japan and the low pressure in the east are temporally enhanced and lead to northerly-northwesterly winds from the Eurasian continent, whereas in the P-type snowfall distribution, the pattern rather temporally weakens due to a weak and/or slow depression over the Sea of Japan. Iwamoto et al (2008) found different local surface wind directions/strengths between the P-type and the M-type snowfalls in the Niigata area. Strong M-type local winds occur in the southward-southeastward direction, whereas weak P-type local winds are directed eastward.…”
Section: Introductionmentioning
confidence: 84%
“…It is empirically and statistically known that there is variability in snowfall distributions in the Japan-Sea side areas, for which the predominant snowfall occurs in the mountainous areas, referred to as mountain-(M-) type snowfall; the other predominant one occurs in the plains, referred to as plain-(P-) type snowfall (Akiyama 1981a, b;Tachibana 1995;Iwamoto et al 2008;Ueda et al 2015). The P-and M-type snowfalls occurring in the Niigata area, one of the heaviest snowfall areas at the Japan-Sea side, have been studied (e.g., Fukaishi 1961;Akiyama 1981a, b;Iwamoto et al 2008). There are three dominant snowfall distributions: the P type, the M type, and a positive/ negative snowfall anomaly in both the plain and the mountainous areas, referred to as the PM type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest decrease was observed in the northwestern Japanese coastal area (Ishizaka 2004, Takeuchi et al 2008, Ishii and Suzuki 2011, Suzuki 2011). This area is highly affected by the winter monsoon; air masses coming from the Asian continent pick up moisture in the Japan Sea and precipitation is enhanced by the orographic effect of the coastal mountain range (Akiyama 1981, Iwamoto et al 2008.…”
Section: Introductionmentioning
confidence: 99%